PHONOLOGICAL CORRESPONDENCE BETWEEN INDONESIAN AND MADURESE LANGUAGE : A STUDY OF ETHNOGRAPHY OF COMMUNICATION - Anita Rahmah Dewi; Siti Aisah (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2021)
Vernacular or local language as general used by several communities which is admitted by cultural symbol of those communities. Such as Madurese Language. Madurese language is interesting to be analyzed due to the various dialect which available. Therefore, this study aims to investigate the language variety which exists in Madurese language. It also elaborates the phonological correspondence which is occurred between Indonesian and Madurese language. This study uses ethnography of communication approach that is formulated by Dell Hymes. Furthermore, to conduct this study, the library research method is applied to serve the data. This study finds out some different dialects and speech levels which exist in Madurese language. subsequently, some various phonological correspondences also occur between Indonesian and Madurese language